(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
“Health is wealth” is a famous proverb applicable to all people. However even after decades of independence, India has yet to achieve its optimum goal in health sector. Although public awareness regarding government initiatives is increasing, the health infrastructure remains inefficient. The planning of healthcare and welfare services is becoming increasingly significant due to profound social and economic impact of addressing public health challenges. Efficient utilization of personnel, materials and financial resources is guaranteed by effective health planning. Improving health services efficacy, accessibility and quality is its main objective. Health is fundamental right of every individual and because public health is within a state control, the responsibility for providing medical aid to people of every class and group fall in state administration. Several flagship schemes have been launched to strengthen healthcare system, ensuring that everyone has access to equitable, affordable and high quality care. However, India continues to see substantial discrepancies between rural and urban areas, notably in tribal areas and Gujarat’s The Dangs district is no exception. Guidelines for establishing Primary Health Centre (PHC) and Sub Centre have been issued across country in compliance with the established norms. The current study seeks to determine if the Primary Health Centre and Sub Centre in the area achieve these standards.